Implementing Jesuit Charisms and Core Values in Distance Education - Dickel, Charles Timothy; Ishii-Jordan, Sharon R. (Catholic Education: A Journal of Inquiry and Practice, 2008)
Given the ever-increasing number of students who are taking distance education courses, it seems appropriate to look beyond the explicit, academic curriculum and consider how institutional charisms and core values might be implemented in distance education courses. This article explores the incorporation of charisms and core values in distance education with particular attention to some of those of the Society of Jesus (the Jesuits). Each of the mentioned Jesuit charisms and core values is described and operationalized in terms of distance education for secondary and higher education students. Relevant and practical examples are provided from courses currently being offered.